Development of biofortified rice for reduce stunting rates in South Sumatra Province - Rina Sopiana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2024)
Lack of the element Zn in the body was one of the serious problems of malnutrition in Indonesia because it reduces endurance, productivity and quality of human life, and was one of the factors causing stunting. Stunting is worrying because it can cause problems with a child's growth and development, which is characterized by the child's height being below standard. One of the factors causing stunting is reduced consumption of zinc (Zn), especially in pregnant women and children. Deficiency of the element Zn in the body can be corrected by consuming foods that contain Fe and Zn. This writing aims to inform and convey the idea that one of the efforts that can be made to reduce stunting rates is through the development of Biofortified rice which will produce nutritious rice. To evaluate the impact of rice development, an evaluation was carried out on rice production and its effect on reducing stunting in several districts in South Sumatra. The method used was interviews, recapitulation of primary and secondary data. Biofortified rice cultivation efforts had been carried out in South Sumatra since 2021 in South OKU (1000 ha), in 2022 in Lahat (1000 ha), and in 2023 in eight districts (8000 ha). In general, Biofortified rice production in South OKU Regency (5.28 tons dry Grain/ha) and Lahat Regency (5.08 tons Harvested Dry Grain/ha). Based on the 2021 Indonesian Nutritional Status Survey (INSS) saw a decrease in the average prevalence of stunting in South Sumatra in 2022 to 18.6%, which decreased from 24.8% in 2021, including in Biofortified rice  development districts. Based on the fact that the development of Biofortified rice can be an effort to reduce stunting, The Regional Government was increasingly expanding rice cultivation in almost all districts/cities.